TYPOLOGIE DE LA VÉGÉTATION PAR UNE APPROCHE DE SIGNATURE SPECTRALE DANS LE SUD DU PARC NATIONAL DE LA COMOÉ (NORD-EST CÔTE D’IVOIRE) - Kouassi Konan Edouard; Sangne Yao Charles; Dibi N’da Hyppolyte (European Scientific Journal, ESJ, 2014)
Comoé National park (NPC) located in the North-Eastern of Côte d'Ivoire, is the largest park of West Africa (1.150.000 ha) and has been classified as the world inheritance by UNESCO in 1983. Since 2003, UNESCO classified this park on the list of the reserves in danger. This organization thus recommended a more rigorous management of NPC, with an integration of the bordering populations to this activity. For the installation of such an operation, it is necessary as a preliminary to give a report on the places. It is within this framework that, this study carried out this floristic prospecting. Our first objective was to produce a flora of this area in the South of the park. Then, our preoccupation was to characterize the various biotopes by groups of species and to evaluate their diversities. Using a satellite image, we positioned 30 squares pieces of 5 m side in 5 types of vegetation, with 3 in savannas and 2 in forest. We obtained a flora is rich of 266 species from higher plants, with 177 in the pieces and 89 in the itinerant statements. Floristic diversities decrease from the galleries forests (5,96) to the types III of savannas (4,55), while passing by the forest small islands (5,87), the types I of savannas (5,20) and the types II of savannas (4,66). The species responsible for the diversity of the various ecosystems are the accessory species. For an efficient protection of this flora, it is necessary to centre the observations on this group of species.